Content Marketing, Brand Reputation, and TikTok Affiliate Marketing Performance: The Mediating Roles of Viral Credibility Marketing and Online Trust - Saripermanik Budayanti; Pramono Hari Adi; Refius Pradipta Setyanto (Global Research Collaboration, 2026)
This study investigates the influence of Content Marketing and Brand Reputation on Affiliate Marketing Performance, with Viral Credibility Marketing (VCM) and Online Trust as mediating variables. Using a quantitative approach with Partial Least Squares Structural Equation Modelling (PLS-SEM), data were collected from 170 TikTok affiliates in Indonesia who had a minimum of one year of professional experience. The results reveal that Content Marketing does not directly affect Affiliate Marketing Performance or Online Trust, suggesting that content quality alone is insufficient to drive performance or build trust. In contrast, Brand Reputation positively and significantly affects both Affiliate Marketing Performance and Online Trust, confirming the importance of established brand credibility. VCM significantly affects both Affiliate Marketing Performance and Online Trust, highlighting the role of credible viral content. Online Trust also positively affects Affiliate Marketing Performance. Regarding mediating mechanisms, VCM successfully mediated the relationship between Content Marketing and Affiliate Marketing Performance, as well as between Brand Reputation and Affiliate Marketing Performance. Online Trust mediates the effect of Brand Reputation on Affiliate Marketing Performance but not the effect of Content Marketing on Affiliate Marketing Performance. The novelty lies in introducing VCM, an integrative construct grounded in Diffusion of Innovation Theory, e-WOM Theory, Social Proof Theory, and Trust Transfer Theory. Theoretically, these findings extend trust transfer and social proof theories into affiliate marketing while establishing the boundary conditions for content marketing theory. Practically, affiliates should prioritize credibility cues alongside content quality, companies must consistently manage brand reputation, and policymakers are encouraged to promote transparent affiliate disclosures